Employer-sponsored medical college training as a tool to address healthcare workforce shortages: Student motivation and ways to improve engagement with healthcare organizations - K. V. Kuzmin; L. E. Petrova; V. S. Kharchenko; E. V. Gorelova; E. O. Kostyleva (Kuban Scientific Medical Bulletin, 2026)
Background. While employer-sponsored medical college training is recognized as a vital tool for mitigating healthcare workforce shortages in the public sector, actual organizational and support practices remain inconsistent. Even with a well-established regulatory framework, significant challenges persist, including superficial applicant selection, low student awareness regarding future workplaces, and limited engagement by healthcare facilities in the professional development of sponsored students. Objective. To analyze the advantages, disadvantages, and development prospects of employer-sponsored training from the perspectives of students, medical colleges, and sponsoring healthcare organizations. Methods. The study employed a mixed-methods design that combined qualitative and quantitative approaches, marking its first application to the analysis of employer-sponsored medical college training. This approach uncovered contradictions, underlying motivations, and personal experiences that cannot be revealed through a standardized survey alone, while also verifying the robustness of the findings. An online survey conducted in May–June 2025 included 582 students whose tuition is covered by the regional budget under four-party agreements. Preliminary data were gathered through two focus groups with graduating students ( n = 25), as well as expert interviews with representatives from a medical college and public healthcare organizations ( n = 4). Data analysis involved univariate, bivariate, and comparative analyses of the survey results, alongside a thematic analysis of focus group and expert interview transcripts. Results. A major challenge of employer-sponsored training is the low level of student awareness regarding their future employers; only 84 % of respondents could name specific healthcare organizations, while one in six either declined to answer or stated, “I do not remember,” reflecting a lower level of informed career decision-making even at the initial stage. Expert interviews and focus groups revealed significant variations in applicant selection practices and a lack of standardized procedures. While some healthcare organizations conduct comprehensive interviews with applicants, others limit interaction to formal hiring procedures. Participant feedback is highly illustrative in this regard: “I didn’t even know I was on a sponsored track at first”; “My mom got me the sponsored slot, and I just got in.” Student communication with healthcare organizations remains weak during their studies: a third of respondents have had no contact with their sponsoring organization since signing the contract, and almost half believe they do not have an assigned mentor. As the most significant advantages of this training model, students note guaranteed employment, tuition-free education, and admissions benefits. The main disadvantage is the inability to change healthcare institutions during their studies, with more than half of the respondents identifying this as the most significant limitation. Willingness to work under a sponsored contract is directly linked to future employment conditions; almost 75 % of students note “fair” pay as a key condition. Focus group insights included statements such as “more money, less overtime” and “fair pay, respect, and employee appreciation. Conclusion. The effectiveness of employer-sponsored training is determined not only by the contract itself and guaranteed employment but also by the quality of applicant selection, student awareness, the involvement of healthcare organizations, and the transparency of future working conditions. Our data demonstrate the need for stricter regulations governing selection for sponsored positions, enhanced career counseling, early integration of students into medical organizations, and an optimized mentorship framework.